On homotopically equivalent relations for fiber bundles - Dawood, Suliman; Kilicman, Adem (Elsevier, 2013)
In this paper, we prove the homotopically equivalent relation to the polyhedron property that play an important role in fiber bundle theory over the suspensions of polyhedron space.